Motion control of a robotic arm from a computer using free control software and wireless communication with XBEE modules - Carlos Vélez; Freddy Orosco; M. A. Álvarez (ACI Avances en Ciencias e Ingenierías, 2014)
This document demonstrates the control of a robotic arm wirelessly by using free software. For this, an operator (user) will be the one giving the orders and actions to be taken, using a computer through various input devices and XBEE modules that are part of our communication channel. The fact that the system includes wireless communication allows distancing the operator from the robot arm and thus can reduce risk when working in addition a large number of wires that may hinder or impede the development of any activity is eliminated. The system has several options for handling the mechanical arm which has developed a free software interface that would maximize all basic input devices of the computer. The software in question is the Processing program which allows the arm to be controlled by keyboard, mouse or even using motion detection through a webcam, and to employ USB output port to transmit data through the modules XBEE. Finally have to say that the results obtained in a complete system prototype robotic arm can serve as a basis for developing several applications including, for example, remote rovers.